Decay estimates for a kind of linear wave equations - Li, Ming; Li, Xinfu (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We consider one kind of dissipative wave equations with exponential speed of propagation. An arbitrary power decay rate for the L^2-norm and energy is obtained by using the multiplier method.